Three new genera of the mite family Eviphididae (Acari: Mesostigmata) - Mašán, Peter; Halliday, Bruce (Zootaxa, 2009)
Three new genera of the mite family Eviphididae Berlese are described, based on non-phoretic species that occur in soil. The new genera are Alloseius gen. nov., with type species Iphidosoma pratensis Karg, Pseudoalliphis gen. nov., with type species Alliphis sculpturatus Karg, and Halolaspis gen. nov., with type species Halolaspis hypedon sp. nov. Iphidosoma insolentis Ma, 1997 is transferred to Alloseius gen. nov. A key to the world genera of the family Eviphididae is provided.